Financial Feasibility Analysis of the Keiling Rice Milling Business in Trimulya Village, Onembute Subdistrict, Konawe Regency - Rijal Ma’ruf; Bahari; Abdi (International Journal of Technology and Education Research, 2026)
This study aims to analyze the financial feasibility of a mobile rice milling business in Trimulya Village, Onembute District, Konawe Regency. The research method employed is descriptive quantitative. Data were collected through observation, interviews, and documentation. The results of the analysis indicate that the mobile rice milling business is financially feasible, with a Net Present Value (NPV) of Rp804.673.537, a Net Benefit-Cost Ratio (NBCR) of 10,9, an Internal Rate of Return (IRR) of 75,6%, and a Payback Period (PP) of 1,5 years. Sensitivity analysis shows that the business remains feasible despite a 10% increase in input costs, a 10% decrease in output prices, or a combination of both, as all feasibility indicators continue to meet the criteria for viability. Based on these results, the mobile rice milling business in Trimulya Village is considered feasible to be operated and further developed